2013
DOI: 10.3324/haematol.2013.089334
|View full text |Cite
|
Sign up to set email alerts
|

Integrated safety profile of single-agent carfilzomib: experience from 526 patients enrolled in 4 phase II clinical studies

Abstract: Carfilzomib, a selective proteasome inhibitor, was approved in 2012 for the treatment of relapsed and refractory multiple myeloma. Safety data for single-agent carfilzomib have been analyzed for 526 patients with advanced multiple myeloma who took part in one of 4 phase II studies (PX-171-003-A0, PX-171-003-A1, PX-171-004, and PX-171-005). Overall analyses of adverse events and treatment modifications are presented, as well as specific analyses of adverse events by organ system. Overall, the most common advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
297
1
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(326 citation statements)
references
References 48 publications
13
297
1
15
Order By: Relevance
“…22 In our study, lymphopenia, thrombocytopenia, anemia and neutropenia were the most common Xgrade 3 hematologic AEs, which is similar to those observed with singleagent carfilzomib. 22 Fever and hypokalemia were the most common Xgrade 3 nonhematologic AEs in our study, whereas pneumonia, fatigue and dyspnea were the most common Xgrade 3 nonhematologic AEs with single-agent carfilzomib. 22 One patient (2.7%) had CHF, which compares favorably with the four phase II studies that investigated single-agent carfilzomib, in which 30 patients (5.7%) had Xgrade 3 CHF.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…22 In our study, lymphopenia, thrombocytopenia, anemia and neutropenia were the most common Xgrade 3 hematologic AEs, which is similar to those observed with singleagent carfilzomib. 22 Fever and hypokalemia were the most common Xgrade 3 nonhematologic AEs in our study, whereas pneumonia, fatigue and dyspnea were the most common Xgrade 3 nonhematologic AEs with single-agent carfilzomib. 22 One patient (2.7%) had CHF, which compares favorably with the four phase II studies that investigated single-agent carfilzomib, in which 30 patients (5.7%) had Xgrade 3 CHF.…”
Section: Discussionsupporting
confidence: 85%
“…22 Fever and hypokalemia were the most common Xgrade 3 nonhematologic AEs in our study, whereas pneumonia, fatigue and dyspnea were the most common Xgrade 3 nonhematologic AEs with single-agent carfilzomib. 22 One patient (2.7%) had CHF, which compares favorably with the four phase II studies that investigated single-agent carfilzomib, in which 30 patients (5.7%) had Xgrade 3 CHF. Dyspnea was not observed in our study.…”
Section: Discussionmentioning
confidence: 49%
“…Carfilzomib has been used in combination with lenalidomide and dexamethasone and as a single agent in patients with relapsed and/or refractory MM and varying degrees of renal function (Badros et al , 2013; Niesvizky et al , 2013; Siegel et al , 2013). Whole blood and PBMC samples from patients receiving 15 or 20 mg/m 2 of carfilzomib with 40 mg of dexamethasone and 10, 15 or 25 mg of lenalidomide (study PX‐171‐006) were taken 1 h after the first dose of carfilzomib and analysed for active site activity and occupancy.…”
Section: Resultsmentioning
confidence: 99%
“…11,28 Carfilzomib-based regimens have been generally well tolerated, but concerns for CV toxicity have been raised. 10,[13][14][15]29 Here, we assessed carfilzomib-associated CV AEs in phase 1-3 clinical trials. Across all RRMM phase 3 trials, treatment with carfilzomib was associated with a numeric increase in cardiac AE incidence.…”
Section: Discussionmentioning
confidence: 99%
“…12 In pivotal phase 2 and 3 studies, there has been a reported increase in CV AEs. 10,[13][14][15] In the phase 3 ASPIRE and ENDEAVOR studies, the grade $3 cardiac failure incidence was 3.8% (KRd) vs 1.8% (Rd) and 4.8% (Kd) vs 1.8% (Vd). 10,15 Post hoc analyses of ASPIRE and ENDEAVOR data according to age showed increased cardiac failure risk in elderly patients.…”
Section: Introductionmentioning
confidence: 99%